If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3c + -2(3c + -4) = 4 + -5(2c + -3) Reorder the terms: 3c + -2(-4 + 3c) = 4 + -5(2c + -3) 3c + (-4 * -2 + 3c * -2) = 4 + -5(2c + -3) 3c + (8 + -6c) = 4 + -5(2c + -3) Reorder the terms: 8 + 3c + -6c = 4 + -5(2c + -3) Combine like terms: 3c + -6c = -3c 8 + -3c = 4 + -5(2c + -3) Reorder the terms: 8 + -3c = 4 + -5(-3 + 2c) 8 + -3c = 4 + (-3 * -5 + 2c * -5) 8 + -3c = 4 + (15 + -10c) Combine like terms: 4 + 15 = 19 8 + -3c = 19 + -10c Solving 8 + -3c = 19 + -10c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '10c' to each side of the equation. 8 + -3c + 10c = 19 + -10c + 10c Combine like terms: -3c + 10c = 7c 8 + 7c = 19 + -10c + 10c Combine like terms: -10c + 10c = 0 8 + 7c = 19 + 0 8 + 7c = 19 Add '-8' to each side of the equation. 8 + -8 + 7c = 19 + -8 Combine like terms: 8 + -8 = 0 0 + 7c = 19 + -8 7c = 19 + -8 Combine like terms: 19 + -8 = 11 7c = 11 Divide each side by '7'. c = 1.571428571 Simplifying c = 1.571428571
| 5+5p=1p | | 9(3x-16)+15=6x-24 | | 4-3(6n-3)=95 | | 65+15x= | | 20x=500 | | -4u(u-5)(u-4)=0 | | x(x+6)(x+-4)=24x | | -68-9x=127+6x | | A=1020(1-0.0195)15 | | X+(x+12)=5x | | 12m+5=6+1m | | 13y+15=39 | | 3.2+0.3(18)=0.2(18)+1.4 | | 7(6-4P)+2P= | | -(n-3)+7(3+n)-2n+7n= | | 3(7q+6)=3q | | 3-4k=11 | | -8(1m-6)=88 | | -13m=-3777 | | 2.4(m-3)+8=-8.2 | | 58=2thirdw | | -4(-5n-4)=-144 | | 7(4+3x)=196+3x | | -x+3=40 | | (2x+1)+(3x-3)+(9x)=180 | | 5x-2d+1=15 | | 2=-11k | | A=1020(1-0.195)15 | | -x-3=16 | | 29x+160=73 | | y=0.23x+27 | | 10x+260-5x=450 |